Can endogenous group formation prevent coordination failure? A theoretical and experimental investigation - Philippe Raab (Institute for the Study of Labor (IZA), 2005)
This paper studies the effect of endogenous group formation on the outcome in two types of coordination games with multiple Pareto-ranked equilibria. Endogenous group formation means that in each period players are free to choose among two or more groups within which they want to play the coordination game. In the theoretical part we show that a simple myopic best reply dynamics under endogenous group formation leads to the payoff dominant outcome in both types of coordination games, independently of the initial strategy profile. In the experimental part we test this prediction. Our results show that the accuracy of the theoretical prediction is sensitive to the out-of-equilibrium properties of the respective coordination game. If the collective outcome is very sensitive to unilateral deviations, the coordination failure takes the same form under endogenous group formation as in the case of fixed groups. If, however, the coordination game is sufficiently robust against these unilateral deviations, coordination on the payoff dominant equilibrium is observed for the large majority of subjects under endogenous group formation. Moreover, in the former case we find the emergence of equally sized groups, while in the latter case large groups emerge. Interestingly, the respective group sizes can be interpreted as minimizing the individual's risk of encountering coordination deteriorating players.
Keywords: C72; C91; C92; 330; coordination games; endogenous formation; minimum effort game; median effort game; experiment; Gruppentheorie; Test; Theorie; Nichtkooperatives Spiel; Koordination